(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Uveitis, inflammatory diseases of the eye being in 25 % of cases result in disability-free, that determines the significance and relevance of the study of the pathogenesis of this disease. The aim. Explore the direction and intensity of changes in the parameters of the tissue and humoral immunity in patients with uveitis with different clinical signs. Materials and methods. In 61 patients with uveitis (46 pers. with lesions posterior segment of the eye, 15 — front, among whom 51 people was of chronic disease, and 10 — acute) were examined using standard ophthalmic methods. In the blood plasma parameters of cell studied (T-lymphocytes, T-helpers and T-suppressors) and humoral (B-lymphocytes, immunoglobulins A, M, G) immunity. The results. The role of tissue and humoral immunity in the development of uveitis based on the clinical course of the inflammatory process. Shown a significant increase in the relative content of cytotoxic T lymphocytes and decrease in the index T helper/cytotoxic T-lymphocytes in the localization of uveitis in the posterior segment of the eye. In the acute phase of the process found a significant increase in the relative content of CD3 + and immunoregulatory index. Among the studied parameters of humoral immunity was significantly significant increase in the total-lymphocytes due to lower levels of Ig A in patients with posterior localization of uveitis. Significant differences between the level of the studied parameters of humoral immunity in patients with ostnym and chronic uveitis were found. Conclusions. These results indicate that implementation of an immune response associated with uveitis, primarily with the activation of T-cell immunity, as well as the killer ability of natural killer cells.